Pertanggungjawaban Hukum dan Kerugian Konsumen dalam Pemalsuan BBM: Studi Kasus Pemalsuan Pertamax di SPBU 34.151.39 Tangerang - Achmad Hafizh Sirait; Dede Agus; Jarkasi Anwar (Journal of Contemporary Law Studies, 2025)
This study aims to analyze consumer legal protection against Pertamax fuel This study examines the legal accountability of business actors and the losses suffered by consumers in the Pertamax fuel counterfeiting case at Gas Station 34.151.39 in Tangerang City. The research aims to analyze the extent of consumer protection, the legal responsibilities arising from the distribution of counterfeit fuel, and the violation of good faith principles in business practices. Using a qualitative method with a case study approach, data were obtained through in-depth interviews with consumers and relevant stakeholders, field observations, and analysis of regulatory documents and supervisory reports. The study applies Philipus M. Hadjon’s Legal Protection Theory, covering preventive, repressive, and remedial mechanisms. The findings reveal that fuel adulteration—such as mixing lower-grade fuel with coloring substances to resemble Pertamax—results in significant financial and technical losses, including engine damage and reduced vehicle performance. Legal protection remains ineffective due to weak supervision and limited enforcement against business actors. The gas station operator is legally obligated, under Article 19 of the Consumer Protection Act, to provide compensation through refunds, product replacement, or other statutory remedies. The study concludes that strengthening monitoring, imposing strict sanctions, and enhancing consumer awareness are essential to ensuring effective legal protection and safeguarding consumer rights in fuel distribution.